Crowd-Sourced Evaluation: A Qualitative Study of User-Generated Product Review Videos on ExpoTV.com - Wilson, Kurt (Journal of MultiDisciplinary Evaluation, 2012)
Background: While user-generated videos are typically associated with humorous or shocking videos far removed from the rigorous world of evaluation, this paper explores the potential for utilizing user-generated videos as evaluation data. This topic is addressed through a qualitative pilot study of product review videos available on the ExpoTV.com website. The findings from this important subset of the evaluation field are analyzed with the goal of identifying themes and insights that could be useful to the broad field of evaluation. Purpose: The primary purpose of this study is to identify characteristics or insights about the user-generated content that could serve as a guide for future studies and the development of new theory or methodology to enlarge the scope and relevance of data used in evaluations. Setting: The ExpoTV.com website Intervention: Not applicable. Research Design: Grounded theory. Data Collection and Analysis: User-generated videos downloaded from the ExpoTV.com website. Analyzed in three stages – In Vivo coding, Axial coding and theme identification. Findings: This article finds intriguing strengths to user-generated video as an evaluation data source because user-generated product review videos consistently demonstrate three important elements of evaluation: they provide a description of the product, explain the broader context for both the product and nature of the specific review, and provide an evaluative conclusion that is logically related to specific evaluative descriptions.